Phylogenetic analysis shows that New Zealand isolates of Neonectria ditissima are similar to European isolates - Everett, Kerry R.; Pushparajah, Irene P.S.; Scheper, Reiny W.A. (New Zealand Plant Protection, 2021)
Neonectria ditissima causes a debilitating apple tree canker disease. We determined the efficacy of polymerase chain reaction primers, originally designed for European strains, by sequencing New Zealand strains. The concatenated ribosomal inter-transcribed spacer and β-tubulin gene regions of 17 New Zealand isolates were compared with those of two European strains by phylogenetic analysis. New Zealand and European isolates of N. ditissima were in the same clade, suggesting that there has been little change in these gene regions following introduction to New Zealand. There was 100% homology with Bt-FW135 and Bt-RW284 primers. Based on sequencing 17 New Zealand isolates from several locations, these polymerase chain reaction primers can be relied upon to amplify New Zealand isolates of N. ditissima.